Sistem Informasi dalam Pengendalian Manajemen Perusahaan - Dailami Dailami (Jurnal Ilman: Jurnal Ilmu Manajemen, 2018)
writing this papet aims to find out how pengenalian upper management information systems. The method of writing using the methods of research library from the discussion, it can be concluded that the information required in support of the inplementation of management control syatem in terms of process and structure in order to obtaint information that supports management control system it is necessary to control system information